2014
DOI: 10.1155/2014/801358
|View full text |Cite
|
Sign up to set email alerts
|

Modified Titanium Implant as a Gateway to the Human Body: The Implant Mediated Drug Delivery System

Abstract: The aim of this study was to investigate the efficacy of a proposed new implant mediated drug delivery system (IMDDS) in rabbits. The drug delivery system is applied through a modified titanium implant that is configured to be implanted into bone. The implant is hollow and has multiple microholes that can continuously deliver therapeutic agents into the systematic body. To examine the efficacy and feasibility of the IMDDS, we investigated the pharmacokinetic behavior of dexamethasone in plasma after a single d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
(34 reference statements)
1
22
0
Order By: Relevance
“…Nanoparticles are highly maneuverable and they are often administered via injection [176179]. The response is fast but frequent injections (e.g., insulin for diabetes) compromise the appliance of patients [180]. Also, nanoparticles lacks the capability in forming a scaffold to support the tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles are highly maneuverable and they are often administered via injection [176179]. The response is fast but frequent injections (e.g., insulin for diabetes) compromise the appliance of patients [180]. Also, nanoparticles lacks the capability in forming a scaffold to support the tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The potential use of different biomaterials as drug carriers, aimed to the local treatment of many conditions, has been analysed in many reports, aiming to obtain the ideal "intelligent material" (Brohede et al, 2009;Johnson and Garcia, 2014;Park et al, 2014;Przekora et al, 2014;Vallet-Regi et al, 2007;Vallet-Regi and Ruiz-Hernandez, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, a great deal remains to be learned about the attributes of the Osseogate, the novel route of administration. Although the results of previous studies demonstrated sustained plasma concentrations of a target drug for up to eight weeks (Park et al, 2014a), it is possible that this was due to the unique properties of the drug being evaluated. Therefore, there is a need for continued evaluation of the Osseogate delivery patterns of several drugs with different physicochemical characteristics.…”
Section: Introductionmentioning
confidence: 97%